HUMAN RESOURCE MANAGEMENT INFORMATION SYSTEMS IN SCHOOLS: LITERATURE REVIEW - Putri, Novita (Program Studi Manajemen, Fakultas Ekonomi dan Bisnis, Universitas Timor, 2023)
Human resource management (HRM) is the most important factor in the world of education. HRM is connected to the formation of educational staff and educators, both of which are important components in preparing educational programs. The COVID-19 pandemic, which spread to various parts of the world for several years and reached Indonesia, has made digitalization in the Indonesian education sector, namely schools, adapt more quickly to the era of digitalization than before. Current technological advances have had a positive impact on the world of education, which is inseparable from the management of human resources in schools. This research uses a literature review method by looking for previous research in journals that discuss HR management in organizations (such as schools) and related HRM issues. The purpose of this literature review is to identify related journals and factors that can help in answering the objectives of this research. The data used in the literature review is from 2018 to 2023. By searching on Google Scholar for keywords used by information systems, HRM, and schools, The data collection for this literature review was from national journals. A total of 55 national journal articles were selected based on the key, and after selecting based on the article topic, relevance of the title, and analysis results, there were 15 articles that were suitable. The results of this literature review are that there are several benefits obtained by installing an HRM information system in schools, including: increasing efficiency both in terms of time and performance; improving data management so that data expands more quickly and is more accessible; and educational issues that can focus more on strategic work.